Impact of Communication on Employee Performance of Pharmaceutical Companies in Nepal - Thapa, Namita (Journal of Economics and Management, 2023)
This study aimed to examine the impact of communication on the employee performance of Pharmaceutical Companies in Nepal. The variables included in the study are independent variables of communication, i.e., oral communication, written communication & non-verbal communication, with employee performance as a dependent variable. A descriptive and analytical research design using a questionnaire method on a 5-point Likert scale was used to collect and analyze the data. The study was conducted with a sample size of 115 employees of pharmaceutical companies in Nepal. The data were analyzed using descriptive statistics, correlation, multiple regression analysis, and t-test using SPSS software. The finding of this study provides empirical evidence to the management to ensure effective oral, written & non-verbal communication in the pharmaceutical companies in Nepal. The results of the study showed that only oral communication significantly impacts employee performance, and both written and non-verbal communication have an insignificant impact on employee performance of pharmaceutical companies of Nepal.